1987
DOI: 10.1007/bf00413256
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence from pilosebaceous follicles

Abstract: Fluorescence studies were performed on the extrusions from pilosebaceous follicles. Pressure extractions produced follicle samples which showed fluorescence under Wood's light. The samples were then analysed in a fluorometer giving corrected excitation spectra. The structured emission spectra achieved were interpreted as being due to porphyrins produced by Propionibacterium acnes (P. acnes). Details in the spectra showed close resemblance to spectra from cultured P. acnes cells. The emission spectra showed dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 11 publications
2
45
1
1
Order By: Relevance
“…13) P. acnes are normal inhabitants of human skin, and excrete porphyrins on the skin surface with sebaceous lipid secretion. 40,41) Our previous report showed that P. acnes-derived coproporphyrin produced singlet oxygen under UVA excitation. 13) This finding suggested that skin was always at risk of damage from singlet oxygen generated by daily UV exposure, and that skin surface lipid was the first target of singlet oxygen.…”
Section: Discussionmentioning
confidence: 94%
“…13) P. acnes are normal inhabitants of human skin, and excrete porphyrins on the skin surface with sebaceous lipid secretion. 40,41) Our previous report showed that P. acnes-derived coproporphyrin produced singlet oxygen under UVA excitation. 13) This finding suggested that skin was always at risk of damage from singlet oxygen generated by daily UV exposure, and that skin surface lipid was the first target of singlet oxygen.…”
Section: Discussionmentioning
confidence: 94%
“…However, different opinions have also been published [22,23]. A recent study reported that UVRF correlated with sebum levels in Nigerian acne patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress stimulates the production of a known inhibitor of hair follicles, tumor growth factor-β, in DPC cells, which induces the onset of androgenic alopecia (24). Our previous studies demonstrated that troxerutin has a photoprotective effect against UV radiation on dermal fibroblasts and keratinocytes (6,7), and several clinical and theoretical reports have revealed that UV radiation has negative effects on hair growth through the induction of oxidative stress, acute telogen effluvium and follicular micro-inflammation in follicular stem cells (31)(32)(33). Therefore, countering oxidative stress can be considered an important strategy to overcome stress-or androgen-dependent alopecia, and the results of the present study confirmed that troxerutin inhibited oxidative stress-induced cellular damage in the DPC cells.…”
Section: Discussionmentioning
confidence: 99%